Pendapatan Asli Daerah, Dana Perimbangan, Belanja Modal dan Lain-Lain Pendapatan yang Sah terhadap Kinerja Kuangan di Pemerintah Daerah Gorontalo - Yolanda Kiu; Rigel Nurul Fathah (Financial and Accounting Indonesian Research, 2025)
This study aims to analyze the effect of Regional Original Revenue (PAD), Intergovernmental Transfers, Capital Expenditure, and Other Legitimate Regional Original Revenues on the Financial Performance of the Gorontalo Regional Government. This study employs a quantitative approach using secondary data obtained from regional government financial reports and the Central Statistics Agency (BPS) for the period 2019–2023. The data were analyzed using multiple linear regression analysis through descriptive statistical tests, classical assumption tests, partial (t-test), and simultaneous (F-test) testing. The results indicate that, both partially and simultaneously, the four variables have a positive and significant effect on regional financial performance, with Other Legitimate Regional Original Revenues showing the most dominant influence. These findings highlight that optimizing regional revenue management and improving the efficiency of capital expenditure play crucial roles in enhancing financial performance and strengthening the fiscal independence of the Gorontalo Regional Government.